1,3-Dipolar Cycloaddition in the Preparation of New Fused Heterocyclic Compounds via Thermal Initiation - Martin Porubský; Lukáš Tenora; Milan Potáček (Molecules, 2016)
This paper describes the synthesis of precursors with a benzo[b]furan skeleton for the intramolecular 1,3-dipolar cycloaddition of azomethine ylides prepared from N-substituted 3-allyl-aminobenzo[b]furan-2-aldehydes and secondary amines derived from α-amino acid esters. Reactions were initiated by heating. The products consisted of four fused rings with three stereogenic centers. Their structure and stereochemistry were determined by NMR spectra and X-ray measurements.